1982
DOI: 10.2337/diab.31.1.s89
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Pregnancy and Fetal Development

Abstract: Although the outcome of pregnancy for women with diabetes meilitus has improved in recent years, the infant of the diabetic mother has an increased risk of major clinical problems, particularly in the early neonatal period. These include birth injury due to macrosomia, neonatal hypoglycemia, respiratory distress syndrome, and serious congenital anomalies. Because of the great difficulties encountered during attempts to investigate these problems in clinical research protocols, there is a continuing need to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Streptozotocin-diabetes in rats has been viewed as an appropriate model for studies on foetal and placental development (Farrell et al, 1982). Effects of a moderate dose of streptozotocin used in this study on the mother, foetus and placenta (Table 1) are similar to those reported elsewhere (Mulay & Solomon, 1983).…”
Section: Discussionsupporting
confidence: 73%
“…Streptozotocin-diabetes in rats has been viewed as an appropriate model for studies on foetal and placental development (Farrell et al, 1982). Effects of a moderate dose of streptozotocin used in this study on the mother, foetus and placenta (Table 1) are similar to those reported elsewhere (Mulay & Solomon, 1983).…”
Section: Discussionsupporting
confidence: 73%
“…For example, the "diabetic" state may have been artificially arrived at by either eliminating maternal insulin production or by giving large amounts of glucose or insulin to mother or fetus (2). Fetuses of some of these models (notably the streptozotocin-treated rat with profound maternal and fetal hyperglycemia) are actually small for gestational age rather than macrosomic (18).…”
Section: Discussionmentioning
confidence: 99%
“…Infants of diabetic mothers whose hyperglycemia is inadequately controlled late in gestation appear to have an increased risk of lung immaturity, as manifested by RDS at birth (I). Animal models in which maternal glucose intolerance and consequent fetal hyperglycemia are artificially induced have been developed to study this phenomenon (2). However, important questions concerning maternal-fetal interactions in diabetes and the consequent effects on fetal organ growth and development might be more appropriately addressed by using a model in which the diabetes is genetically determined, therefore occuning spontaneously in the mother (2).…”
mentioning
confidence: 99%
“…The reason for this is not clear, although it has been suggested that the altered hormonal levels, mainly lower glucagon secretion, are responsible [7]. Since insulin does not cross the placenta [8], the fetus of the insulin-induced hypoglycemic mother is subjected to periods of hypoglycemia, and consequent hypoinsulinemia. The damage to the fetus caused by hypoglycemia has been suggested to stem from the total dependence of the fetus on glycolysis for energy during early neurulation; thus, the harmful effect of hypoglycemia is greatly diminished once the capacity for aerobic glucose metabolism is developed during late neurulation [5].…”
Section: Introductionmentioning
confidence: 95%
“…This suppression in turn leads to the necessity of replenishing TCA cycle intermediates via the anaplerotic PC pathway, active only in the glial compartment [27, for review]. This direct effect of insulin on the brain would not be found in the fetus, since insulin does not cross the placenta [8], and thus, the fetus is only hypoglycemic but not hyperinsulinemic.…”
Section: Glucose Flux Via Pc Versus Pdh In the Hypoglycemic Rabbit Brainmentioning
confidence: 99%